Implementasi Program Penggunaan Aplikasi Qlue dalam Penanganan Sampah di Dinas Lingkungan Hidup dan Kebersihan Kota Kupang - Laura Eveline E. Theedens; Hendrik Toda; Made N. D Andayana (Jurnal Administrasi Publik, 2022)
The purpose of this study is to determine and analyze the implementation of the Qlue application in waste management at the Environment and Hygiene Service. The research methodology was descriptive study with a qualitative approach. The results of the study indicate that the implementation of the qlue application, especially in the issue of waste management, has not been optimal. This is due to a lack of communication between implementers, as field implementers do not fully comprehend the qlue application's functionality. Due to a lack of socialization, many citizens in Kupang City are clueless of the qlue application. There are still limitations of both human resources and supporting facilities in terms of resources. Also, due to the various difficulties experienced in the field, there are differences  knowledge and commitment among implementers. There are no special regulations regarding the use of the qlue application because it is not equipped with SOPs, especially in the field of  waste management. The absence of a particular team or unit in reacting to waste reports via the application is the final point.